Pemanfaatan Limbah Kulit Pisang Menjadi Pupuk Organik Cair Anti Hama Dengan Penambahan EM-4 - Devi Kurnia Sari; Rosalia Dwi Werena; Hasrul Anwar; Rizka Mayasari; Miftahul Djana (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The decomposition process of organic waste, including banana peels, can produce greenhouse gases such as methane. These gases contribute to climate change and global warming if not managed properly. One way to utilize banana peel waste is by converting it into liquid organic fertilizer, which can help farmers produce high-quality liquid organic fertilizer at an affordable price. The impact of using chemical fertilizers and pesticides includes the disruption of soil nutrient balance and pesticide residue content in food products. Based on this, research has been conducted by combining organic fertilizer material from banana peel waste with organic pesticide material from yam bean and galangal waste, thus providing a dual function as an organic fertilizer and a biopesticide in one package. This serves as an effective solution for addressing the scarcity of organic fertilizers and pesticides.